The accuracy of fine needle aspiration biopsy to diagnose breast neoplasm - Hifdza Faza Felisha; Hanggoro Tri Rinonce; Sumadi Lukman Anwar; Ery Kus Dwianingsih (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2019)
Breast lump is a very common complaint among women, especially during the reproductive year. Fine needle aspiration biopsy (FNAB) is a less invasive procedure. It is usually performed as an initial diagnosis prior to the operative procedure. The accuracy of the FNAB in Indonesia needs to be elaborated. The study aimed to evaluate the sensitivity and specificity of FNAB in diagnosing breast neoplasm. This is a retrospective study with cross sectional design, involving 145 patients with breast lump who underwent FNAB and histopathology examination in Dr. Sardjito General Hospital, Yogyakarta, from 2012 to 2014. Data analysis showed that female to male ratio was 23. 2:1 commonly occurred at 41-50 years old. Forty-one cases (28.28%) diagnosed as a benign lesion with fibrocystic changes as the most frequentcase (11.19%). The malignant case was 104 cases (71.72%) with ductal carcinoma as the highest case (51.49%). FNAB achieved a sensitivity of 85.58%, a specificity of 100% and a total accuracy of 89.66% in determining the benign or malignant breast lump. The accuracy, sensitivity and specificity of FNAB in diagnosing ductal carcinoma were 83.58%, 85.51% and 81.54%, respectively. The accuracy, sensitivity and specificity of FNAB to diagnose fibrocystic changes lesion were 85.82%, 26.67% and 93.28%, respectively. FNAB can be used as an alternative diagnostic tool to diagnose breast neoplasm. It provides rapid, cheaper, effective, valuable, and less invasive procedure in diagnosis of breast lump.